A preparation method of Y4Al2O9 / Y2O3 eutectic ceramic powder and spherical feed

By preparing Y4Al2O9/Y2O3 eutectic ceramic spherical feed, the problem of performance degradation of ceramic matrix composite materials for aero engines in high temperature and corrosion environments is solved, and the effect of providing wear and corrosion protection at higher temperatures is achieved.

CN115093225BActive Publication Date: 2025-02-14INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210488159.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-06
Publication Date
2025-02-14
Estimated Expiration
2042-05-06

AI Technical Summary

Technical Problem

Existing ceramic-based composite materials for aircraft engines deteriorate and fail at high temperatures and corrosion environments, requiring a coating material that can provide wear and corrosion protection at higher temperatures.

Method used

Using Y4Al2O9/Y2O3 eutectic ceramic powder and spherical feed, high-purity eutectic ceramic spherical feed is prepared through mechanical mixing, solid phase reaction, spray drying and granulation and sintering treatment to meet plasma spraying, laser cladding or super Sonic flame spraying requirements.

Benefits of technology

The prepared Y4Al2O9/Y2O3 eutectic ceramic spherical feed has the characteristics of dense and smooth surface, tight internal bonding, uniform particle size distribution, good spherical shape and good fluidity, and can provide excellent wear resistance and resistance at higher temperatures. Corrosion performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003630072730000011
    Figure HDA0003630072730000011
  • Figure HDA0003630072730000021
    Figure HDA0003630072730000021
  • Figure HDA0003630072730000022
    Figure HDA0003630072730000022
Patent Text Reader

Abstract

The present invention belongs to the field of protective coatings, and specifically relates to a method for preparing a Y4Al2O9 / Y2O3 eutectic ceramic powder and a spherical feed. The powder is a eutectic ceramic powder raw material of Y4Al2O9 and Y2O3, and the two are mixed in a eutectic composition ratio (molar ratio Y2O3:Al2O3=70.5:29.5). Nano-scale or submicron-scale Al2O3 powder and Y2O3 powder are used as raw materials, and the Y4Al2O9 / Y2O3 eutectic ceramic powder raw material is prepared through mechanical mixing and solid phase reaction, and then spray drying granulation and high-temperature sintering are performed to prepare a Y4Al2O9 / Y2O3 eutectic ceramic spherical feed with a smooth surface, tight internal bonding, uniform particle size distribution, high sphericity and good fluidity. The feed is suitable for wear-resistant ceramic coatings or thermal barrier / environmental barrier integrated protective coatings for high-temperature alloys and ceramic-based composite materials, and meets the feeding requirements for preparing related coatings by plasma spraying, laser cladding or supersonic flame spraying.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of protective coatings, and specifically relates to a method for preparing a Y4Al2O9 / Y2O3 eutectic ceramic powder raw material and a spherical feed suitable for wear-resistant ceramic coatings or thermal barrier / environmental barrier integrated protective coatings for high-temperature alloys and ceramic-based composite materials, which meets the requirements of plasma spraying, laser cladding or supersonic flame spraying for preparing relevant coatings. Background Art

[0002] The development of aviation technology has put forward higher requirements on the efficiency and thrust of aircraft engines. In order to improve the thrust-to-weight ratio of aircraft engines, the temperature of the air inlet before the turbine is also required to be continuously increased. The above requirements put forward a series of performance requirements for high-temperature structural materials used in aircraft engines, such as high temperature resistance, wear resistance and corrosion resistance. At present, typical high-temperature structural materials used in aircraft engines include single crystal high-temperature alloys, SiC f / SiC ceramic matrix composites, and Al2O 3f / Al2O3 and other oxide ceramic matrix composites. Compared with high-temperature alloys, ceramic matrix composites have the characteristics of low density, high temperature resistance and low thermal conductivity. However, when SiC is used as a structural component of an aircraft engine, f / SiC and Al2O 3f Ceramic-based composite materials such as MgO / Al2O3 are subject to high-speed particle erosion in the engine gas environment, as well as erosion by corrosive media such as CMAS (CaO-MgO-Al2O3-SiO2 low-melting-point environmental deposits), high-temperature water vapor and molten salts. Their performance degrades and fails quickly, so a protective coating with excellent high-temperature resistance, wear resistance, high-temperature mechanical properties, and resistance to water vapor and CMAS corrosion must be coated on their surface.

[0003] Eutectic ceramics of alumina and aluminate have the characteristics of high melting point, strong wear resistance, good high-temperature mechanical properties, and excellent resistance to high-temperature water vapor and CMAS corrosion. They are new structural materials with great application prospects. For example, Y3Al5O prepared by directional solidification 12 / Al2O3 eutectic ceramics, after being kept in a 1700℃ water vapor environment for 100 to 200 hours, have no significant decrease in bending strength, showing excellent high-temperature mechanical properties and resistance to water vapor corrosion. 12 The Y3Al5O3 coating has no obvious cracks on the service surface under the high load conditions of 2000N and 500rpm, showing excellent high-speed load capacity and wear resistance. 12 The excellent performance of Y3Al5O3 eutectic materials mainly comes from the strong chemical bonds between atoms in eutectic aluminate materials and the unique eutectic microstructure: the eutectic phase is distributed continuously and intertwined along the solidification direction.12 The mutual restraint and assistance of the Al2O3 phase in three-dimensional space significantly improves the mechanical properties of Y4Al2O9 / Y2O3 eutectic ceramics. 12 / Al2O3 has a higher eutectic temperature and may have better high temperature resistance; at the same time, compared with the Al2O3 matrix phase, the Y2O3 matrix phase has better high temperature mechanical properties, water vapor and CMAS corrosion resistance. It can be expected that Y4Al2O9 / Y2O3 eutectic ceramics are expected to become a protective coating material for aircraft engines that can meet the needs of higher service temperatures, stronger wear resistance and corrosion resistance.

[0004] Commonly used preparation technologies for ceramic protective coatings for aircraft engines mainly include: plasma spraying, laser cladding and supersonic flame spraying. Atmospheric plasma spraying has the advantages of moderate porosity of the prepared coating, low thermal conductivity, and a wide range of powder preparation (both high melting point and low melting point can be applied); laser cladding technology can produce coatings with small heat-affected zones, good microstructures, and excellent bonding properties; supersonic flame spraying has a wider and longer flame and higher spraying efficiency than atmospheric plasma spraying. These typical preparation methods must be based on the preparation technology of high-quality powder raw materials. In order to ensure a uniform and dense protective coating, conventional powders need to be light in weight and have good fluidity.

[0005] To sum up, the establishment of Y4Al2O9 / Y2O3 eutectic ceramic powder and its spherical feeding preparation method for plasma spraying, laser cladding or supersonic flame spraying will provide basic material support and technical reserves for the new generation of aircraft engines with new protective coatings with excellent high temperature resistance, wear resistance, water vapor resistance and CMAS corrosion resistance. Summary of the invention

[0006] Aiming at the demand of the new generation of aircraft engines for high temperature resistant, wear resistant and corrosion resistant protective ceramic coatings, the purpose of the present invention is to provide a method for preparing Y4Al2O9 / Y2O3 eutectic ceramic powder and spherical feed. The powder raw material is suitable for wear-resistant ceramic coatings or thermal barrier / environmental barrier integrated protective coatings for high temperature alloys or ceramic-based composite materials, so that it meets the requirements of preparation processes such as plasma spraying, laser cladding or supersonic flame spraying.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a Y4Al2O9 / Y2O3 eutectic ceramic powder and a spherical feed material. The powder is a eutectic ceramic powder raw material of Y4Al2O9 and Y2O3, which are mixed at a eutectic component ratio (molar ratio of Y2O3:Al2O3=70.5:29.5); Al2O3 powder and Y2O3 powder are used as raw materials, and the Y4Al2O9 / Y2O3 eutectic ceramic powder raw material is prepared through mechanical mixing and solid phase reaction; spray drying granulation and high-temperature sintering are then performed to prepare a Y4Al2O9 / Y2O3 eutectic ceramic spherical feed material with a smooth surface, tight internal bonding, uniform particle size distribution, high sphericity and good fluidity. The meaning of the eutectic composition ratio is: the relative ratio of the two phases Y4Al2O9 and Y2O3 in the powder composition is the ratio at which the two phases can undergo a eutectic reaction under specific temperature conditions (eutectic temperature). Specifically in the present invention, the molar ratio of Y2O3 to Al2O3 is 70.5:29.5.

[0009] The preparation method of the Y4Al2O9 / Y2O3 eutectic ceramic powder and spherical feed material comprises the following specific steps:

[0010] (1) using nano-scale or submicron-scale aluminum oxide powder and yttrium oxide powder as raw materials, the mass fraction of Al2O3 powder is in the range of 5wt% to 25wt%, the mass fraction of Y2O3 powder is in the range of 75wt% to 95wt%, and the sum of the mass percentages of the two is 100wt%;

[0011] (2) mixing alumina powder and yttrium oxide powder, by mixing raw material powder and ball milling solvent, and then sequentially ball milling and drying to obtain a uniformly mixed Al2O3-Y2O3 mixture powder;

[0012] (3) subjecting the obtained Al2O3-Y2O3 mixed powder to a solid phase reaction at a temperature T1 to obtain a Y4Al2O9 / Y2O3 eutectic ceramic powder raw material;

[0013] (4) mixing the Y4Al2O9 / Y2O3 eutectic ceramic powder raw material with deionized water, a binder, a dispersant and a pH adjuster using a ball mill to obtain a uniform and stable slurry;

[0014] (5) agglomerating the obtained slurry with a spray drying device to obtain agglomerated Y4Al2O9 / Y2O3 eutectic ceramic spherical feed;

[0015] (6) The Y4Al2O9 / Y2O3 eutectic ceramic spherical feed material after agglomeration treatment is post-sintered at a temperature T2, cooled, and sieved to obtain the Y4Al2O9 / Y2O3 eutectic ceramic spherical feed material.

[0016] The method for preparing the Y4Al2O9 / Y2O3 eutectic ceramic powder and spherical feedstock, in step (1), the particle size of the Al2O3 powder is nanometer or submicron, and the particle size range is 50 to 500nm; the particle size of the Y2O3 powder is nanometer or submicron, and the particle size range is 50 to 500nm.

[0017] The method for preparing the Y4Al2O9 / Y2O3 eutectic ceramic powder and spherical feedstock, in step (2), the mixing of the Al2O3-Y2O3 mixture powder is completed by using Al2O3 powder and Y2O3 powder in a planetary ball mill, the medium is anhydrous ethanol, the mass ratio of the mixture powder to anhydrous ethanol is (1:2) to (2:1), the mass ratio of the ball material is (1:2) to (4:1), the ball mill speed is 120 to 350 rpm, and the mixing ball milling time is 2 to 24 hours.

[0018] The method for preparing the Y4Al2O9 / Y2O3 eutectic ceramic powder and spherical feedstock, in step (3), obtains the Y4Al2O9 / Y2O3 eutectic ceramic powder raw material by a solid phase reaction method, and the solid phase reaction temperature T1 is 1200°C to 1600°C, and the insulation time is 2 to 24h.

[0019] The method for preparing the Y4Al2O9 / Y2O3 eutectic ceramic powder and spherical feedstock, in step (4), the solid content of the slurry is 30wt% to 70wt%; the binder is selected from at least one of polyvinyl alcohol, paraffin, sodium lignin sulfonate or glycerol, and the addition amount thereof is 0.1wt% to 2.0wt%; the dispersant is selected from at least one of polyacrylamide, polymethyl methacrylic acid, polyethyleneimine, sodium silicate, polyethylene glycol, and the addition amount thereof is 0.1wt% to 2.0wt%; the pH adjuster is selected from at least one of glacial acetic acid, hydrochloric acid, and tetramethylammonium water, and the addition amount thereof is 0.3wt% to 1.5wt%; the ball-to-material mass ratio is (1:2) to (2:1), the ball mill speed is 160 to 350rpm, and the mixing ball milling time is 6 to 24h.

[0020] The method for preparing the Y4Al2O9 / Y2O3 eutectic ceramic powder and spherical feedstock, in step (5), the agglomeration treatment adopts a spray drying equipment, and its parameters are: the inlet temperature is 100-300°C, the outlet temperature is 100-200°C, the peristaltic pump speed is 10-30rpm, the atomizer speed is 11000-14000rpm, the nozzle pressure is 0.05-0.30MPa, and the air intake volume is 1.5-3.0m 3 / min.

[0021] The method for preparing the Y4Al2O9 / Y2O3 eutectic ceramic powder and spherical feedstock, in step (6), the sintering temperature T2 is 1000°C to 1500°C, the holding time is 2 to 5 hours, and the particle size range of the spherical feedstock after screening is 5 to 85 μm.

[0022] The design idea of ​​the present invention is:

[0023] The present invention is aimed at ceramic protective coatings for high-temperature structural components of new-generation aircraft engines, especially wear-resistant ceramic coatings or integrated thermal barrier / environmental barrier protective coatings. In order to meet the performance requirements of resistance to sand / high-speed airflow erosion wear and high-temperature water vapor / CMAS / molten salt corrosion at higher temperatures, high-melting-point Y4Al2O9 / Y2O3 eutectic ceramics are selected as target materials. On the one hand, both Y4Al2O9 and Y2O3 have strong interatomic chemical bonds, and are high-melting-point, high-corrosion-resistant oxide ceramics with good high-temperature performance; on the other hand, by utilizing the eutectic reaction characteristics of Y4Al2O9 and Y2O3, a unique eutectic phase distribution can be formed in the preparation process. The microstructure is continuously and intertwined, and the matrix phase and the reinforcement phase are mutually constrained and auxiliary-enhanced in the three-dimensional space. The eutectic morphology further improves its mechanical properties significantly. Considering that the protective coating is prepared by plasma spraying, laser cladding or supersonic flame spraying, in order to meet the requirements of powder particle size control, fluidity and bulk density during the spraying process, the powder is further agglomerated by spray drying equipment, and agglomerated powder with a specific particle size distribution is screened out. This can ensure that the Y4Al2O9 / Y2O3 powder is easier to melt and deposit during the coating preparation process, promote the eutectic reaction between the two, and ensure the uniformity and density of the protective coating.

[0024] The advantages and beneficial effects of the present invention are:

[0025] 1. The present invention selects Y3Al5O 12 / Al2O3 eutectic ceramics have a new system Y4Al2O9 / Y2O3 with a higher eutectic point temperature. This material has better high temperature resistance. At the same time, compared with Al2O3, Y2O3 has better resistance to water vapor and CMAS corrosion, which can provide eutectic materials with better wear and corrosion resistance.

[0026] 2. Different from the conventional method of directly mixing yttrium oxide and alumina powder and then spray drying and granulating, the present invention first obtains Y4Al2O9 / Y2O3 eutectic ceramic powder raw material through a solid phase reaction method, thereby ensuring the uniformity of the distribution of yttrium aluminate phase and yttrium oxide phase (or these two Chinese characters are directly written as chemical formulas), and then spray drying and granulation treatment is performed, which helps to obtain eutectic ceramic spherical feed with good sphericity, uniform size, tight internal bonding and stability.

[0027] 3. The eutectic ceramic spherical feed designed by the present invention can be used to prepare high-quality protective coatings. The base material is widely applicable, including high-temperature alloys, SiC f / SiC ceramic matrix composites and oxide ceramic matrix composites.

[0028] 4. The particle size distribution of the Y4Al2O9 / Y2O3 eutectic ceramic spherical feed for spraying prepared by the present invention is 10-60 μm, and the bulk density is 0.8-1.5 g / cm 3 The fluidity is 70-150s / 50g, the surface is smooth and the interior is dense, with good fluidity, which meets the needs of spherical feeding for preparation technologies such as plasma spraying, laser cladding or supersonic flame spraying. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the XRD spectrum of the Y4Al2O9 / Y2O3 eutectic ceramic powder raw material in Example 1. In the figure, the horizontal axis 2θ represents the diffraction angle (degrees), and the vertical axis Intensity represents the relative intensity (arb.units).

[0030] Figure 2(a)-Figure 2(b) (a) Scanning electron microscope image and (b) particle size distribution diagram of the Y4Al2O9 / Y2O3 eutectic ceramic powder raw material in Example 1. In Figure 2(b), the horizontal axis Particle size represents the particle size (μm), and the vertical axis Volume (%) represents the volume percentage (%).

[0031] Figure 3(a)-Figure 3(c) (a) Scanning electron microscope surface morphology image and (b) scanning electron microscope cross-sectional morphology image and (c) particle size distribution diagram of the Y4Al2O9 / Y2O3 eutectic ceramic spherical feed prepared in Example 2. In Figure 3(c), the abscissa Particle size represents the particle size (μm), and the ordinate Volume (%) represents the volume percentage (%).

[0032] Figure 4 This is the element (Al, Y, O) surface scanning distribution diagram of the Y4Al2O9 / Y2O3 eutectic ceramic spherical feed prepared in Example 3. DETAILED DESCRIPTION

[0033] The present invention is further described below by the following embodiments, which are only used to illustrate the present invention but not to limit the present invention.

[0034] In the specific implementation process, the preparation method of the Y4Al2O9 / Y2O3 eutectic ceramic powder and spherical feed of the present invention comprises the following specific steps:

[0035] (1) Alumina powder and yttrium oxide powder are used as raw materials, the mass fraction of Al2O3 powder is in the range of 5wt% to 25wt% (preferably 15wt%), the mass fraction of Y2O3 powder is in the range of 75wt% to 95wt% (preferably 85wt%), and the sum of the mass percentages of the two is 100wt%;

[0036] (2) mixing alumina powder and yttrium oxide powder, by mixing raw material powder and ball milling solvent, and then sequentially ball milling and drying to obtain a uniformly mixed Al2O3-Y2O3 mixture powder;

[0037] (3) subjecting the obtained Al2O3-Y2O3 mixed powder to a solid phase reaction at a temperature T1 to obtain a Y4Al2O9 / Y2O3 eutectic ceramic powder raw material;

[0038] (4) mixing the Y4Al2O9 / Y2O3 eutectic ceramic powder raw material with deionized water, a binder, a dispersant and a pH adjuster using a ball mill to obtain a uniform and stable slurry;

[0039] (5) agglomerating the obtained slurry with a spray drying device to obtain agglomerated Y4Al2O9 / Y2O3 eutectic ceramic spherical feed;

[0040] (6) performing a post-sintering treatment on the Y4Al2O9 / Y2O3 eutectic ceramic spherical feed after agglomeration treatment at a temperature T2, cooling, and screening to obtain a Y4Al2O9 / Y2O3 eutectic ceramic spherical feed with a smooth surface, tight internal bonding, uniform particle size distribution, high sphericity and good fluidity;

[0041] In step (1), the particle size of Al2O3 powder is nanometer or submicron, and the particle size range is 50 to 500 nm (preferably 200 nm); the particle size of Y2O3 powder is nanometer or submicron, and the particle size range is 50 to 500 nm (preferably 200 nm).

[0042] In step (2), the mixing of the mixture powder Al2O3 powder and the Y2O3 powder is carried out in a planetary ball mill, the medium is anhydrous ethanol, the mass ratio of the mixture powder to anhydrous ethanol is (1:2) to (2:1) (preferably 1:1), the mass ratio of the ball material is (1:2) to (4:1) (preferably 2:1), the ball mill speed is 120 to 350 rpm (preferably 260 rpm), and the mixing ball milling time is 2 to 24 h (preferably 6 h).

[0043] In step (3), the Y4Al2O9 / Y2O3 eutectic ceramic powder raw material is obtained by a solid phase reaction method, and the solid phase reaction temperature T1 is 1200°C to 1600°C (preferably 1400°C), and the insulation time is 2 to 24h (preferably 6h).

[0044] In step (4), the solid content of the slurry is 30wt% to 70wt% (preferably 50wt%); the binder is selected from at least one of polyvinyl alcohol, paraffin, sodium lignin sulfonate or glycerol (preferably polyvinyl alcohol), and the addition amount thereof is 0.1wt% to 2.0wt% (preferably 1.0wt%); the dispersant is selected from at least one of polyacrylamide, polymethacrylic acid, polyethyleneimine, sodium silicate, and polyethylene glycol (preferably polyethylene glycol), and the addition amount thereof is 0.1wt% to 2.0wt% (preferably 1.0wt%); the pH adjuster is selected from at least one of glacial acetic acid, hydrochloric acid, and tetramethylammonium water (preferably glacial acetic acid), and the addition amount thereof is 0.3wt% to 1.5wt% (preferably 1.0wt%); the ball-to-material mass ratio is (1:2) to (2:1) (preferably 1:1), the ball mill speed is 160 to 350rpm (preferably 260rpm), and the mixing ball milling time is 6 to 24h (preferably 6h).

[0045] In step (5), the agglomeration treatment adopts a spray drying equipment, and its parameters are: inlet temperature is 100-300°C (preferably 200°C), outlet temperature is 100-200°C (preferably 150°C), peristaltic pump speed is 10-30rpm (preferably 20rpm), atomizer speed is 11000-14000rpm (preferably 12000rpm), nozzle pressure is 0.05-0.30MPa (preferably 0.20MPa), air volume is 1.5-3.0m 3 / min (preferably 2.0m 3 / min).

[0046] In step (6), the sintering temperature T2 is 1000°C to 1500°C (preferably 1200°C), the holding time is 2 to 5 hours (preferably 3 hours), and the particle size range of the spherical feed after screening is 5 to 85 μm (preferably 40 μm).

[0047] Below, the present invention is further described in detail by examples.

[0048] The performance test information in the following embodiments is as follows:

[0049] 1. Morphology observation:

[0050] The morphology of the agglomerate powder was observed using a Zeiss Supra 35 field emission scanning electron microscope;

[0051] 2. X-ray diffraction analysis:

[0052] Phase analysis was performed using an X-ray diffractometer (Rigaku D / max-2400, Tokyo, Japan);

[0053] 3. Liquidity test:

[0054] The agglomerate powder was tested for fluidity using a BT-200 metal powder fluidity tester (Hall flowmeter) produced by Dandong Better Instrument Co., Ltd.

[0055] 4. Bulk density test:

[0056] The bulk density of the agglomerate powder was tested by using a BT-100 bulk density meter produced by Dandong Better Instrument Co., Ltd.; the particle size distribution of the agglomerate powder was tested by using a Mastersizer 2000 laser particle size analyzer produced by Malvern Panalytical.

[0057] Example 1

[0058] In this embodiment, the preparation method of Y4Al2O9 / Y2O3 eutectic ceramic powder and spherical feed material comprises the following specific steps:

[0059] (1) Using nano-sized Al2O3 powder and Y2O3 powder as raw materials, the original particle sizes of Al2O3 powder are 50-100 nm, Y2O3 powder is 50-100 nm, the mass fraction of Al2O3 powder is 15wt%, the mass fraction of Y2O3 powder is 85wt%, and the sum of the mass percentages of the two is 100wt%;

[0060] (2) Using anhydrous ethanol as the medium, the raw materials (Al2O3 powder and Y2O3 powder) and anhydrous ethanol were placed in a ball mill at a mass ratio of 1:1 and ball milled for 6 h, followed by drying and sieving to obtain a uniformly mixed Al2O3-Y2O3 mixture powder; the ball milling parameters were as follows: the ball-to-material mass ratio was 2:1, and the ball mill speed was 260 rpm;

[0061] (3) keeping the obtained Al2O3-Y2O3 mixture powder in a muffle furnace at 1400°C for 6 hours to obtain a Y4Al2O9 / Y2O3 eutectic ceramic powder raw material;

[0062] (4) Deionized water, binder polyvinyl alcohol (PVA), dispersant polyethylene glycol (PEG), and pH adjuster glacial acetic acid (CH3COOH) were added to the eutectic ceramic powder raw material, and mixed for 6 hours using a ball mill to obtain a uniform and stable slurry; the solid content of the slurry was 50wt%, the amount of the binder added was 1.0wt%, the amount of the dispersant added was 1.0wt%, and the amount of the pH adjuster added was 1.0wt%; the ball milling parameters were as follows: the ball-to-material mass ratio was 2:1, and the ball mill speed was 260rpm;

[0063] (5) The obtained slurry is subjected to powder agglomeration treatment by spray drying equipment to obtain agglomerated Y4Al2O9 / Y2O3 eutectic ceramic spherical feed; the spray drying granulation parameters are: air inlet temperature 200°C, air outlet temperature 150°C, peristaltic pump speed 20 rpm, atomizer speed 12000 rpm, nozzle pressure 0.20 MPa, air inlet volume 2.0 m 3 / min;

[0064] (6) The Y4Al2O9 / Y2O3 eutectic ceramic spherical feed after agglomeration treatment was post-sintered in a muffle furnace at 1200°C, kept warm for 3 hours, and then cooled. After 300-700 mesh screening, a Y4Al2O9 / Y2O3 eutectic ceramic spherical feed for spraying with a smooth surface, tight internal bonding, good fluidity, and good high-temperature stability was obtained.

[0065] The obtained eutectic ceramic powder and eutectic ceramic spherical feed were tested, and the results are as follows:

[0066] like Figure 1 As shown, the eutectic ceramic powder obtained after being kept at 1400℃ in a muffle furnace for 6 hours has high purity and contains only Y4Al2O9 / Y2O3 without other substances.

[0067] As shown in Figure 2(a), the scanning electron microscope image of the eutectic ceramic powder raw material shows that the particle size distribution of the Y4Al2O9 / Y2O3 eutectic ceramic powder raw material obtained after solid phase reaction sintering is uniform and the particle size is small.

[0068] As shown in Figure 2(b), the laser particle size distribution of Y4Al2O9 / Y2O3 eutectic ceramic powder shows that the particle size distribution is 0.1-1.3 μm, D 50 About 0.4μm.

[0069] The fluidity test shows that the fluidity of the Y4Al2O9 / Y2O3 eutectic ceramic spherical feed for spraying is 135s / 50g.

[0070] The bulk density test shows that the bulk density of the Y4Al2O9 / Y2O3 eutectic ceramic spherical feed for spraying is 1.40g / cm 3 .

[0071] Example 2

[0072] In this embodiment, the preparation method of Y4Al2O9 / Y2O3 eutectic ceramic powder and spherical feed material comprises the following specific steps:

[0073] (1) Submicron Al2O3 powder and Y2O3 powder are used as raw materials, wherein the original particle size is 100-500 nm for Al2O3 powder and 100-500 nm for Y2O3 powder, the mass fraction of Al2O3 powder is 20 wt%, the mass fraction of Y2O3 powder is 80 wt%, and the sum of the mass percentages of the two is 100 wt%;

[0074] (2) Using anhydrous ethanol as the medium, the raw materials (Al2O3 powder and Y2O3 powder) and anhydrous ethanol were placed in a ball mill at a mass ratio of 1:1 and ball milled for 6 h, followed by drying and sieving to obtain a uniformly mixed Al2O3-Y2O3 mixture powder; the ball milling parameters were as follows: the ball-to-material mass ratio was 2:1, and the ball mill speed was 260 rpm;

[0075] (3) keeping the obtained Al2O3-Y2O3 mixture powder in a muffle furnace at 1500°C for 6 hours to obtain a Y4Al2O9 / Y2O3 eutectic ceramic powder raw material;

[0076] (4) Deionized water, binder polyvinyl alcohol (PVA), dispersant polyethylene glycol (PEG), and pH adjuster glacial acetic acid (CH3COOH) were added to the eutectic ceramic powder raw material, and mixed using a ball mill to obtain a uniform and stable slurry; the solid content of the slurry was 50wt%, the amount of the binder added was 1.0wt%, the amount of the dispersant added was 1.0wt%, and the amount of the pH adjuster added was 1.0wt%; the ball milling parameters were as follows: the ball-to-material mass ratio was 2:1, and the ball mill speed was 260rpm;

[0077] (5) The obtained slurry is subjected to powder agglomeration treatment by spray drying equipment to obtain agglomerated Y4Al2O9 / Y2O3 eutectic ceramic spherical feed; the spray drying granulation parameters are: air inlet temperature 200°C, air outlet temperature 150°C, peristaltic pump speed 20 rpm, atomizer speed 12000 rpm, nozzle pressure 0.20 MPa, air inlet volume 2.0 m 3 / min;

[0078] (6) The Y4Al2O9 / Y2O3 eutectic ceramic spherical feed after agglomeration treatment was post-sintered in a muffle furnace at 1200°C, kept warm for 3 hours, and then cooled. After 300-700 mesh screening, a Y4Al2O9 / Y2O3 eutectic ceramic spherical feed for spraying with a smooth surface, tight internal bonding, good fluidity, and good high-temperature stability was obtained.

[0079] The obtained Y4Al2O9 / Y2O3 eutectic ceramic powder and eutectic ceramic spherical feed were tested, and the results are as follows:

[0080] As shown in Figure 3(a), the surface of the Y4Al2O9 / Y2O3 eutectic ceramic spherical feed is dense and smooth, with good sphericity and uniform particle size distribution.

[0081] As shown in Figure 3(b), the cross-sectional view of the Y4Al2O9 / Y2O3 eutectic ceramic spherical feedstock shows that the spherical feedstock is tightly bonded internally and has a high density.

[0082] As shown in Figure 3(c), the laser particle size distribution of the Y4Al2O9 / Y2O3 eutectic ceramic spherical feed is uniform, with a particle size distribution of 20 to 65 μm, D 50 About 39μm.

[0083] The fluidity test shows that the fluidity of the Y4Al2O9 / Y2O3 eutectic ceramic spherical feed for spraying is 127s / 50g.

[0084] The bulk density test shows that the bulk density of the Y4Al2O9 / Y2O3 eutectic ceramic spherical feed for spraying is 1.44g / cm 3 .

[0085] Example 3

[0086] In this embodiment, Y4Al2O9 / Y2O3 eutectic ceramic powder and spherical feedstock thereof are obtained according to the process of Embodiment 1. The difference from Embodiment 1 is that submicron Al2O3 powder and Y2O3 powder are used as raw materials, and the original particle sizes are 100-500nm for Al2O3 powder and 100-500nm for Y2O3 powder.

[0087] like Figure 4 As shown in the figure, the element (Al, Y, O) surface scanning distribution test results of the Y4Al2O9 / Y2O3 eutectic ceramic spherical feed are shown. It can be seen from the figure that the Al, Y, and O elements are evenly distributed.

[0088] The results of the embodiment show that the Y4Al2O9 / Y2O3 eutectic ceramic powder of the present invention is a eutectic ceramic powder raw material of Y4Al2O9 and Y2O3; the Y4Al2O9 / Y2O3 eutectic ceramic composite powder is prepared by mechanical mixing and solid phase reaction, and then spray drying and granulation are carried out, and then high-purity Y4Al2O9 / Y2O3 eutectic ceramic spherical feed is prepared by agglomeration treatment. The spherical feed has the characteristics of dense and smooth surface, tight internal bonding, uniform particle size distribution, good sphericity and good fluidity, and can meet the requirements of plasma spraying, laser cladding or supersonic flame spraying for preparing wear-resistant ceramic coatings or integrated thermal barrier / environmental barrier protective layers for high-temperature alloys or ceramic-based composite materials.

[0089] Although the present invention has been disclosed as above in some embodiments, it is not intended to limit the present invention. Any technical personnel in this field can make possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the main purpose and scope of the present invention. Therefore, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing Y4Al2O9 / Y2O3 eutectic ceramic spherical feed, characterized in that: Using Al2O3 powder and Y2O3 powder as raw materials, Y4Al2O9 / Y2O3 eutectic ceramic powder raw materials are prepared through mechanical mixing and solid phase reaction; spray drying granulation and high temperature sintering are then carried out to prepare Y4Al2O9 / Y2O3 eutectic ceramic spherical feed with smooth surface, tight internal bonding, uniform particle size distribution, high sphericity and good fluidity; The preparation method of the Y4Al2O9 / Y2O3 eutectic ceramic spherical feed material comprises the following specific steps: (1) using nano-scale or submicron-scale aluminum oxide powder and yttrium oxide powder as raw materials, the mass fraction of Al2O3 powder is in the range of 15wt% to 20wt%, the mass fraction of Y2O3 powder is in the range of 80wt% to 85wt%, and the sum of the mass percentages of the two is 100wt%; (2) mixing alumina powder and yttrium oxide powder, by mixing raw material powder and ball milling solvent, and then sequentially ball milling and drying to obtain a uniformly mixed Al2O3-Y2O3 mixture powder; (3) subjecting the obtained Al2O3-Y2O3 mixed powder to a solid phase reaction at a temperature T1 to obtain a Y4Al2O9 / Y2O3 eutectic ceramic powder raw material; (4) mixing the Y4Al2O9 / Y2O3 eutectic ceramic powder raw material with deionized water, a binder, a dispersant and a pH adjuster using a ball mill to obtain a uniform and stable slurry; (5) agglomerating the obtained slurry with a spray drying device to obtain agglomerated Y4Al2O9 / Y2O3 eutectic ceramic spherical feed; (6) performing a post-sintering treatment on the agglomerated Y4Al2O9 / Y2O3 eutectic ceramic spherical feed at a temperature T2, cooling, and screening to obtain a Y4Al2O9 / Y2O3 eutectic ceramic spherical feed; In step (1), the particle size of Al2O3 powder is nanometer or submicron, and the particle size ranges from 50 to 500 nm; the particle size of Y2O3 powder is nanometer or submicron, and the particle size ranges from 50 to 500 nm; In step (2), the mixing of Al2O3-Y2O3 mixture powder is completed by using Al2O3 powder and Y2O3 powder through a planetary ball mill, the medium is anhydrous ethanol, the mass ratio of the mixture powder to anhydrous ethanol is (1:2) to (2:1), the ball-to-material mass ratio is (1:2) to (4:1), the ball mill speed is 120 to 350 rpm, and the mixing ball milling time is 2 to 24 hours; In step (3), a Y4Al2O9 / Y2O3 eutectic ceramic powder raw material is obtained by a solid phase reaction method, and the solid phase reaction temperature T1 is 1200°C to 1600°C, and the holding time is 2 to 24 hours; In step (4), the solid content of the slurry is 30wt% to 70wt%; the binder is selected from at least one of polyvinyl alcohol, paraffin, sodium lignin sulfonate or glycerol, and the addition amount thereof is 0.1wt% to 2.0wt%; the dispersant is selected from at least one of polyacrylamide, polymethacrylic acid, polyethyleneimine, sodium silicate and polyethylene glycol, and the addition amount thereof is 0.1wt% to 2.0wt%; the pH adjuster is selected from at least one of glacial acetic acid, hydrochloric acid and tetramethylammonium water, and the addition amount thereof is 0.3wt% to 1.5wt%; the ball-to-material mass ratio is (1:2) to (2:1), the ball mill speed is 160 to 350rpm, and the mixing ball milling time is 6 to 24h; In step (5), the agglomeration treatment adopts a spray drying equipment, and its parameters are: inlet temperature is 100-300°C, outlet temperature is 100-200°C, peristaltic pump speed is 10-30rpm, atomizer speed is 11000-14000rpm, nozzle pressure is 0.05-0.30MPa, air volume is 1.5-3.0m 3 / min; In step (6), the sintering temperature T2 is 1000°C to 1500°C, the holding time is 2 to 5 hours, and the particle size range of the spherical feed after screening is 5 to 85 μm.

Citation Information

Patent Citations

  • Spraying material, spraying slurry, preparing method of spraying material, forming method of sprayed coating, sprayed coating, and sprayed member

    CN111826601A